2022
DOI: 10.3389/fgene.2021.758596
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis Based on Genomic Instability for Prognostic Prediction in Lower-Grade Glioma

Abstract: Background: Lower-grade gliomas (LGGs) are a heterogeneous set of gliomas. One of the primary sources of glioma heterogeneity is genomic instability, a novel characteristic of cancer. It has been reported that long noncoding RNAs (lncRNAs) play an essential role in regulating genomic stability. However, the potential relationship between genomic instability and lncRNA in LGGs and its prognostic value is unclear.Methods: In this study, the LGG samples from The Cancer Genome Atlas (TCGA) were divided into two cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Recent studies found the role of long non-coding RNA in doxorubicin-induced cardiomyopathy, lncRNA NONMMUT015745 inhibits doxorubicin-mediated cardiomyocytes apoptosis by regulating the Rab2A-p53 axis [27], METTL14 silencing suppresses the ferroptosis of cardiomyocyte in doxorubicin-induced mice[28].TGFB2-AS1 has been reported in breast cancer, glioma, lung adenocarcinoma, gastric cancer, and other tumor diseases, and more importantly, the limited molecular biological role of TGFB2-AS1 in some diseases has been illustrated [29]. Studies have shown that mutations in the TGFBR1 and TGFB2-AS1 genes were associated with myopia in preschoolers, mediated by the TGF-β signaling pathway [30]; loss of TGFB2-AS1 signi cantly promoted Apoptosis of HepG2 liver cancer cells and inhibited migration and invasion [31], and TGFB2-AS1 interacted with the Core subunit of SWI/SNF complex, SMARCA4 to inhibit the expression of target genes TGFB2 and SOX2, ultimately inhibiting the breast Cancer progression [32].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found the role of long non-coding RNA in doxorubicin-induced cardiomyopathy, lncRNA NONMMUT015745 inhibits doxorubicin-mediated cardiomyocytes apoptosis by regulating the Rab2A-p53 axis [27], METTL14 silencing suppresses the ferroptosis of cardiomyocyte in doxorubicin-induced mice[28].TGFB2-AS1 has been reported in breast cancer, glioma, lung adenocarcinoma, gastric cancer, and other tumor diseases, and more importantly, the limited molecular biological role of TGFB2-AS1 in some diseases has been illustrated [29]. Studies have shown that mutations in the TGFBR1 and TGFB2-AS1 genes were associated with myopia in preschoolers, mediated by the TGF-β signaling pathway [30]; loss of TGFB2-AS1 signi cantly promoted Apoptosis of HepG2 liver cancer cells and inhibited migration and invasion [31], and TGFB2-AS1 interacted with the Core subunit of SWI/SNF complex, SMARCA4 to inhibit the expression of target genes TGFB2 and SOX2, ultimately inhibiting the breast Cancer progression [32].…”
Section: Discussionmentioning
confidence: 99%
“… 242 A novel signature of five GlnLncRNAs has been screened to predict prognosis in glioma. 243 , 244 Mutations of seven genes have been detected with better OS in gastric cancer patients receiving anti-PD-1/PD-L1 treatment. 245 In addition, the deep learning method has also been used to predict the clinical benefits of anti-PD-L1/PD-1 therapy in advanced NSCLC patients.…”
Section: Clinical Dilemmas Of Icbmentioning
confidence: 99%
“…ML has made considerable strides in the previous several decades, developing complicated learning algorithms and effective pre-processing methods [ 22 , 23 ]. The development of Artificial Neural Networks (ANNs) into Deep Neural Network (DNN) topologies with gradually boosted DL learning capabilities was one of these breakthroughs [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%